Analysis of Tea Plant (Camellia Sinensis) Farming in the PTPN 7 Regional 1 Gunung Dempo Pagar Alam, South Sumatra, Indonesia - supli rahim (Indonesian Soil Science Society of South Sumatra in Collaboration With Soil Science Department, Sriwijaya University, 2026)
The low selling price of tea in the country by PTPN 7 Regional 1 Gunung Dempo Pagar Alam is currently causing the selling price of tea plant shoots to be increasingly cheaper as indicated by the decreasing number of farming revenues and the low farming income received by the state-owned company. The aim of this research is to describe the farming performance carried out by PTPN 7. Apart from that, the main aim of this research is to analyze the value of tea farming starting from the value of farming revenues, farming costs and farming income. The research results show that that tea farming is still feasible and profitable to continue to be developed. This is evidenced by the B/C ratio value which exceeds 1, which indicates that each unit cost incurred still generates profit. In addition, the R/C ratio value in all PTPN 7 plantation divisions ranges from, which means that for every IDR 1 of total farming costs incurred, the company earns revenue of Rp 1,24. Thus, tea farming at the research location still makes a positive contribution to the company’s income and has good sustainability prospects.